FLATTENING IN SHEAR ZONES UNDER CONSTANT VOLUME: A THEORETICAL EVALUATION - Mandal N.; Chakraborty C.; Kumar Samanta S. (My University, 2001)
This paper presents a theoretical model based on strain energy and work rate calculations that evaluates the possible degrees of flattening in finite, ductile shear zones with rigid and deformable walls under constant volume conditions. The principal parameters governing the ratio of bulk flattening and shear rates (Sr=b/b) in shear zones with rigid walls are found to be: (1) the length to width ratio (Df; measured in the normal section parallel to the extrusion direction), and (2) the inclination of shear zone normal (α) with the bulk compression direction. Narrow and long shear zones (Df>10) are characterized by low Sr ratios, implying little flattening in the shear zone even when α is low (in the order of a few degrees). Accordingly, the kinematical vorticity number Wk is close to one when Df is large (>10) or α is high (>20°), and is much less than one if Df or α are low. The stretching rate of shear zone walls relative to the shear zone (Rf) is an additional parameter that controls the degree of flattening in shear zones with deformable walls. For given Df and α values the flattening rate increases with increasing relative stretching rate Rf, and is significant at large values of Rf. Likewise the kinematical vorticity number Wk shows an inverse relation with the relative stretching rate of shear zone walls.
Keywords: SHEAR ZONES; STRAIN ENERGY; VORTICITY; WORK RATE